Science experimental methods assisted video tutorials as an innovation for distance learning during COVID-19 pandemic - Melati Arifina Alanis; Fina Indriyani; Anggraita Febriana Putri; Laifa Rahmawati (Universitas Negeri Yogyakarta, 2021)
Science learning during COVID 19 pandemic had not been optimally implemented. This research aimed to discuss a new learning strategy, called science experimental accompanied by video tutorials as a distance learning innovation. A study literature method was used in this article. The experimental method was carried out in four stages, namely initial experiment, verification, concept application, and evaluation. This makes distance learning more effective and efficient. Students can develop thoughts, imaginations, and attitudes through exploration; foster interest and motivation to learn, and assisting in learning activities to achieve learning objectives without any limitations on distance and time. Demonstrations in this learning strategy can also be repeated and all students can understand the material.